2022
DOI: 10.3390/su14031576
|View full text |Cite
|
Sign up to set email alerts
|

Social Climate and Psychological Response in the First Wave of the COVID-19 Pandemic in a Greek Academic Community

Abstract: This study examines how the social climate was associated with the psychological response during the first wave of the COVID-19 pandemic. Using a structural equation model linking the economic crisis to the social climate (pandemic fear, social and psychological distress, civil protection, and population’s response) and to the psychological response (perspectives of life and reconsidering values), we tested their multivariate relationships in a Greek academic community sample. At the first level of the model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…A number of recent studies have examined the hazardous impacts of COVID-19 on psychological disorders [8,11,12]. A meta-analysis reported that the pooled prevalence of anxiety and depression was high during the COVID-19 pandemic (33% [95% confidence intervals (CI) = 28-38%] for anxiety and 28% [95% CI = 23-32%] for depression) in the general population [12].…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies have examined the hazardous impacts of COVID-19 on psychological disorders [8,11,12]. A meta-analysis reported that the pooled prevalence of anxiety and depression was high during the COVID-19 pandemic (33% [95% confidence intervals (CI) = 28-38%] for anxiety and 28% [95% CI = 23-32%] for depression) in the general population [12].…”
Section: Introductionmentioning
confidence: 99%
“…Adult education, beyond the times of compulsory training, has a great impact on our society. After the global pandemic, the segment of the adult population has been affected in a very different way from the young [4]. This project is an initiative with farreaching repercussions for members, the adult teachers; and the impact is multiplied when considering that it has reached other indirectly related people, such as the readers of the publications or the students who will receive the training by the teachers involved in the project.…”
Section: Introductionmentioning
confidence: 99%